Catalytic Gas‐phase Fluorination of Hexachlorobutadiene to 1, 2‐Dichlorotetrafluorocyclobutene over Cr/Zn‐based Catalysts. Issue 6 (23rd February 2018) - He, Jinwei; Zhang, Mengxue; Zhou, Biao; Zhou, Xiaomeng
Abstract : In this paper, the gas‐phase fluorination of hexachlorobutadiene (HCBD) to synthesize 1, 2‐dichlorotetrafluorocyclobutene (DTB) was carried out over a series of Cr/M/Zn catalysts (M = Ni, Co, Cu, In, Al). The influence of prefluorination by different fluorinating agents (HF, 95%HF + 5%Cl2, 95%HF + 5%O2, CF2 O, CF2 Cl2 ) on catalytic performance of Cr/Co/Zn sample was also investigated. The addition of prompters to the Cr/Zn catalyst improved remarkably its catalytic properties. The Cr/Ni/Zn catalyst exhibited the best catalytic activity (1.318 mmol/h/g) at 390 °C and the Cr/Co/Zn catalyst showed the best DTB selectivity (42.5%) at 350 °C. Compared to that of gaseous HF, the catalytic performance of the Cr/Co/Zn catalyst after treatment by HF + O2 and CF2 O increased considerably, whereas for HF + Cl2 and CF2 Cl2 it showed little effect. In order to identify the different species (Cr─O, Cr─F, CrO x F y ) present on catalysts' surface and determine their exact role, these catalysts before and after the reaction were characterized by X‐ray photoelectron spectroscopy. It was found that the concentration of the various species was responsible for the activity and lifetime of catalysts. Moreover, a possible reaction route is proposed based upon the product distribution. The most feasible formation pathway of DTB proceeded via the cyclization of C4 Cl4 F2 or C4 Cl3 F3 to yield c‐C4 Cl4 F2 and c‐C4 Cl3 F3 followed by further the Cl/F exchange. Abstract : The gas‐phase fluorination of hexachlorobutadiene to synthesize 1, 2‐dichlorotetrafluorocyclobutene was carried out over Cr/Zn‐based catalysts. The influence of prefluorination by different fluorinating agents on the catalytic performance of Cr/Zn‐based catalyst was investigated. Various catalysts before and after the reaction were characterized by XPS to identify the different species present on catalysts' surface and determine their exact role.